Novel selective adsorption and photodegradation of BPA by molecularly imprinted sulfur doped nano-titanium dioxide. (20th November 2020) - Zhou, Guangzhu; Cao, Yiyun; Jin, Yuqin; Wang, Cuizhen; Wang, Yue; Hua, Chunyu; Wu, Sai
Abstract: To achieve selective adsorption of bisphenol A (BPA) and synergy between photocatalysis and adsorption, a molecular imprinting surface-polymerized nanoparticles loaded on sulfur-doped titanium dioxide hollow spheres (MICST) with the large specific surface area was composed by a chemical method. Firstly, with the aid of surfactants CTAB and SDS, uniform sulfur doped titanium dioxide particles (CST) was synthesized, then the molecularly imprinted polymer layers loaded on the surface, and finally molecular imprinted sulfur-doped titanium dioxide was got after the template molecular were removed. TEM, SEM, EDS, FTIR, BET, and XRD were employed to characterize materials. The specific area measured by BET test was 160 m 2 /g. The parameters including contact time, pH and selectivity were evaluated and optimized systematically. Additionally, the adsorption capacity and selectivity as well as the photodegradation activity were investigated. The maximum adsorption capacity of BPA was 191 mg/g which could be proved by the Langmuir adsorption model. It is superior to most of the reported imprinted photocatalysts in literature. Moreover, the effect of the amount of imprinted polymers was studied for the photodegradation effect. The prepared materials can be a significant candidate for the treatment of recalcitrant organic pollutants in wastewater. Graphical abstract: Image 1 Highlights: Molecular imprinted sulfur-doped TiO2 was synthesized with aid of CTAB and SDS. Specific surface area of MICST is 160 m 2 /g and maximum adsorption capacity is 191 mg/g. The material shows novel adsorption and excellent photodegradation of BPA.